Retraction: SNHG5 promotes proliferation and induces apoptosis in melanoma by sponging miR-155. Issue 39 (7th September 2022) - Yan, Lu; Wang, Suihai; Li, Yue; Tognetti, Linda; Tan, Rui; Zeng, Kang; Pianigiani, Elisa; Mi, Xiangbin; Li, Hui; Fimiani, Michele; Rubegni, Pietro
Abstract : Retraction of 'SNHG5 promotes proliferation and induces apoptosis in melanoma by sponging miR-155' by Lu Yan et al., RSC Adv., 2018, 8, 6160–6168, ; https://doi.org/10.1039/C7RA12520H .